The art of betrayal life and death in the British Secret Service - Corera, Gordon (Weindenfeld & Nicolson, 2011)
From Afghanistan to the Congo, from Moscow to the back streets of London, these are the stories of the men and women who have worked on the front line of Britain's secret wars. And the truth is often more remarkable than the fiction.